Kedudukan Perempuan Dalam Masyarakat Hukum Adat Melayu Riau - Geofani Milthree Saragih; Yoga Triwanda; Zainul Akmal (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2021)
The purpose of this paper is to determine the position and role of women in the Riau Malay customary law community and to find out the Rights and Obligations of Women in Leadership and Election of Riau Malay Customary Heads. It was found for the first time that the position and role of women in indigenous peoples in Riau differed between regions. This is because the customary system in Riau also varies from one region to another. The two rights and obligations of women in the Leadership and Election of Customary Heads are not too big. women do not even have the right to become tribal leaders, but in certain areas women have the special right to reject the chosen adat leader. This may result in re-election, provided it is in accordance with custom.